2017
DOI: 10.20960/nh.874
|View full text |Cite
|
Sign up to set email alerts
|

Valoración Nutricional Con La Situación Funcional Tras Sufrir Un Ictus.

Abstract: Palabras clave:Ictus. Mini Nutritional Assessment. Malnutrición. Dependencia. ResumenObjetivo: valorar el estado nutricional (EN) del paciente a los tres meses de sufrir un ictus y establecer la relación del EN con la recuperación funcional y las complicaciones en este periodo. Material y métodos: estudio observacional y transversal que evaluó el EN de pacientes mayores de 65 años a los tres meses de presentar un ictus. El EN se valoró mediante el Mini Nutritional Assessment (MNA). Se recogieron datos sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
5
4
0
Order By: Relevance
“…At T1, 42 subjects (28 subjects ≥65 years old and 14 subjects <65 years old) were at high risk of malnutrition (63.6%). The results of this study are similar to those of previous studies [3,41]. Malnutrition is associated with dysphagia.…”
Section: Discussionsupporting
confidence: 92%
“…At T1, 42 subjects (28 subjects ≥65 years old and 14 subjects <65 years old) were at high risk of malnutrition (63.6%). The results of this study are similar to those of previous studies [3,41]. Malnutrition is associated with dysphagia.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that 40% of post-stroke patients were at a high risk of malnutrition, a finding similar to that reported by previous studies in Spain (46%) and France (48%) ( 19 , 22 ). Yet, it was much lower than the 84% to 91% prevalence in two Korean studies ( 17 18 ).…”
Section: Discussionsupporting
confidence: 92%
“…Further, the present study showed socioeconomic status determinants such as income, education, and employment status to be associated with increased odds of malnutrition risk, similar to the findings of a study in Spain ( 22 ). However, only employment status remained significant in the multivariate logistic analysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations